Perceptions and reported practices of teacher leadership by Saudi teachers, principals and supervisors in Saudi Arabia - Alhumaid, Musaad Abdulrahman (2025)
This research investigates teacher leadership in selected public schools within Riyadh's Educational Directorate, Saudi Arabia. It explores the perceptions of key stakeholders: principals, supervisors, and teachers, concerning teacher leadership, the factors that empower or inhibit teachers to lead, and the professional development and nurturing of teacher leadership. The study is framed by Grant’s teacher leadership model and three related theories, communities of practice, distributed leadership, and professional learning communities. A nested case study approach was adopted to select two contrasting schools, assessed through their annual evaluations. The qualitative research design combined interviews, observations, focus groups, and reflective essays, involving participants with at least two years of teaching experience.